Educational Support for the Tetebatu Nature School Pilot Program in East Lombok - Marham Jupri Hadi; Meiyanti Widyaningrum; Baiq Salkiah (Universitas Muhammadiyah Malang, 2025)
The Nurul Azhar Educational, Social and Cultural Institute (LPSB) is an institution that operates in the field of developing human resources, improving community welfare and maintaining the culture of the Sasak tribe, especially in Tetebatu Village. To improve human resources in the village, LPSB Nurul Azhar established a nature school with the aim of producing a generation that cares about the environment and maintains the customs that have been inherited by the founding fathers of the village. However, the managers of this nature school do not yet have an understanding of environmental and cultural-based education. For this reason, this community service program aims to assist the administrators in establishing the Tetebatu Nature School. This collaborative initiative, involving the Faculty of Teacher Training and Education at the University of Nahdlatul Wathan Mataram, the Beruga' Alam Institute, and LPSB Nurul Azhar, focused on developing the school’s Vision, Mission, Goals, and Targets; designing the school’s curriculum; and introducing the concept and practice of nature schools and educational tourism-based learning.